2020
DOI: 10.1108/ijwbr-07-2019-0043
|View full text |Cite
|
Sign up to set email alerts
|

Wine consumers in British Columbia, Canada

Abstract: Purpose The purpose of this study is to redirect wine producer marketing strategies in British Columbia (BC) to better market their wine to the next generation of local consumers and compete against foreign imports. Design/methodology/approach This study was conducted using representative data collected from BC wine consumers through a survey of 500 participants and subsequent focus groups to better understand and interpret the findings. Findings The findings confirm that the growth of wine sales in BC is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Knowing the impact of ethnocentrism on the intention to purchase local wine can help local companies increase the intention to purchase local wine by developing marketing campaigns that target ethnocentrism. Previous studies have focused on consumption but only in a specific group such as Millennials [84] by using other analysis methods such as the Tobit regression model [85] rather than the PLS-SEM technique that allows determination of the route of effects and was used in the present study.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…Knowing the impact of ethnocentrism on the intention to purchase local wine can help local companies increase the intention to purchase local wine by developing marketing campaigns that target ethnocentrism. Previous studies have focused on consumption but only in a specific group such as Millennials [84] by using other analysis methods such as the Tobit regression model [85] rather than the PLS-SEM technique that allows determination of the route of effects and was used in the present study.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…Qenani-Petrela and Wolf claimed that premium quality is more desirable to Baby Boomers than to Millennials [51]. The grape variety was verified as the less important attribute for younger generation consumers than older ones, according to [49], while, in most recent studies, Millennials are also less interested in grape variety than Generation X and Baby Boomers [10]. Tait et al indicated that Baby Boomers are willing to pay significantly more for country-of-origin attributes than either Millennials or Generation X consumers [55].…”
Section: Conceptual Framework and Hypothesismentioning
confidence: 99%
“…As the industry has matured, competition has grown in intensity and complexity, while the preferences and customs associated with wine consumption have changed and become more fragmented with new emerging market segments, such as the Millennials (Generation Y) and Generation Z [3,[9][10][11][12]. In this new scenario, wine companies should focus on forecasting the nature of expansion and increasingly unstable demand, and what their direct and indirect competitors can offer.…”
Section: Introductionmentioning
confidence: 99%